KUALITAS PRODUK PENGEMBANGAN PERANGKAT PENILAIAN PORTOFOLIO PADA MATERI POKOK ASAM DAN BASA - Lestari, Pertiwi Indah (STKIP Pembangunan Indonesia Makassar, 2016)
Portofolio assessment is basically assessing student works individually on a subject. Student with portfolio assessment can show differences in the ability to complete the tasks assigned by the teacher from time to time and can be compared to other students' work. The use of any portfolio assessment in trials can describe portfolio assessment tools that can increase student enthusiasm for mengepresikan ability in tasks given portfolio. The purpose of this study was to determine the quality of the product development portfolio of assessment tools in the subject matter of acids and bases. This research was conducted at SMA Negeri 1 Sungguminasa class XI Natural Sciences 5 (NS 5) with the number of students 40 people and the research subject is the portfolio assessment in the subject matter of acids and bases. The research instrument used is the observation sheet keterlaksanaan device portfolio assessment, validation sheet, and a student questionnaire responses. The analysis is the analysis of quantitative data to explain the validity, effectiveness and practicality of assessment tools. The results showed that the quality of the portfolio assessment tools developed have valid criteria, practical, and effective that overall it has met the criteria of validity and reliability. Keterlaksanaan devices are implemented entirely in software quality assessment means practical use. Achievement of students achieving grades portfolio classical completeness 80%, the positive response of students on the use of assessment tools portfolio and the correlation coefficient is positive category means the effective use of portfolio assessment.